Behavioral counseling to overcome online game addiction - Riri Oktavia (Education and Social Sciences Review, 2021)
This research is intended to find out the behaviors arising from the dependency of playing online game on SMP PGRI 1 Padang students which include the factors that cause dependency, psychological condition arising from online game dependence and the effects arising from addiction to play online game. This research approach is qualitative research with case study research based on respondents and information as data source material in the process of collecting data used observation and interview techniques, where after the data is obtained then analyzed using qualitative descriptive analysis. Based on this research that the subject of DL dependency to play online games becauses of the online gaming facilities he has at home is very supportive for DL playing online games, also because of the social factors of the same peers as online game dependence the principal gives the trust to the counselor to solve it including collaboration with DL parents. The results show that behavioral konseling can help to change client behavior in online game dependence.